2005
DOI: 10.1161/01.str.0000181066.23213.8f
|View full text |Cite
|
Sign up to set email alerts
|

The Existence and Evolution of Diffusion–Perfusion Mismatched Tissue in White and Gray Matter After Acute Stroke

Abstract: Background and Purpose-Although white matter is a potential target of acute stroke therapy, there is uncertainty about its relative resistance to ischemia and whether it is capable of mounting a penumbral response. To explore these issues further, we examined the differential effects of ischemia on gray and white matter using magnetic resonance (MR) perfusion-diffusion mismatch after acute stroke. Methods-MR imaging studies were performed within 12 hours in patients with initial hemispheric ischemic stroke."At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 30 publications
1
57
0
Order By: Relevance
“…Although no previous similar study is available for a comparison, our finding is consistent with the notion that WM may be more resistant to ischemia compared with GM. [1][2][3][4] Experimental studies also support this notion. 4 In humans, although the fate of WM versus GM has rarely been studied, our results are consistent with the available data, irrespective of the imaging approach.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Although no previous similar study is available for a comparison, our finding is consistent with the notion that WM may be more resistant to ischemia compared with GM. [1][2][3][4] Experimental studies also support this notion. 4 In humans, although the fate of WM versus GM has rarely been studied, our results are consistent with the available data, irrespective of the imaging approach.…”
Section: Discussionmentioning
confidence: 71%
“…4 In humans, although the fate of WM versus GM has rarely been studied, our results are consistent with the available data, irrespective of the imaging approach. [1][2][3]9,10 For instance, a positron emission tomography study using the hypoxia tracer 18 F-misonidazole found salvageable tissue in WM at later time points than in GM, suggesting that the former has a slower evolution toward infarction. 2 At earlier time points and using perfusion DWI, the same investigators again emphasized the greater resistance of WM to ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these analyses were performed using as an outcome metric the volume of a region-of-interest (ROI) defined by the difference between an acute data set and the outcome image [9,10,11]. For instance, it has been shown that an unsupervised clustering technique such as ISODATA (Iterative Self-Organizing Data Analysis) can utilize combined MRI data sets from the acute phase [2,12] and the subacute phase [5] post-stroke to predict final infarct volume and thus produce a time-independent surrogate MRI outcome predictor [13,14,15,16,17]. However ISODATA has some significant drawbacks.…”
Section: Introductionmentioning
confidence: 99%